DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON ARTICULATE STORYLINE FOR CIVICS SUBJECTS IN ELEMENTARY SCHOOL - SR Danial, Daniaty; Hidayat, Syarip; Madasseri, Sameer Babu (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2025)
The limited learning resources used by teachers in the classroom and the inability of teachers to use technology as a learning tool are the main causes of students' disinterest in learning. To increase the interest of fourth grade elementary school students in Civics, this research aims to create interactive learning materials based on the Artiqulate Storyline thematic map. The five steps of the ADDIE development model of analysis, design, development, implementation and evaluation form the basis of this research methodology. A total of 15 students, media experts, and material experts are the subjects in this study. Three data collection methods were used: questionnaires, interviews, and observations. Descriptive and categorical data analysis was used to determine the feasibility of the media created. With the findings from the material expert testing of 92% which is classified as very good, and from the media expert of 94% which can also be classified as very good, the research results obtained by Artiqulate Storyline-based interactive media can be declared feasible. Meanwhile, the statement is considered valid based on the findings of the student questionnaire response sheet, which shows that the average validity result of r count for the validation level of the student learning interest questionnaire is 0.598. With a reliability value of 0.925, it falls into the excellent category as well. Based on the results of the trial, this interactive media with Artiqulate Storyline is suitable for use by teachers to support the delivery of material and encourage student enthusiasm.